2016
DOI: 10.5194/acp-16-635-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric polarimetric effects on GNSS radio occultations: the ROHP-PAZ field campaign

Abstract: Abstract. This study describes the first experimental observations showing that hydrometeors induce polarimetric signatures in global navigation satellite system (GNSS) signals. This evidence is relevant to the PAZ low Earth orbiter, which will test the concept and applications of polarimetric GNSS radio occultation (RO) (i.e. ROs obtained with a dualpolarization antenna). A ground field campaign was carried out in preparation for PAZ to verify the theoretical sensitivity studies on this concept (Cardellach et… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…The main payload of PAZ is an X-band synthetic aperture radar (SAR), decoupled from and not used by the ROHP-PAZ experiment. The GNSS PRO technique was confirmed further in an experimental field campaign from a mountain top (Padullés et al, 2016a). A preliminary data-processing technique to resolve precipitation structures from GNSS PRO was introduced by Padullés et al (2016b), but they showed that it would work only under certain limited conditions.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The main payload of PAZ is an X-band synthetic aperture radar (SAR), decoupled from and not used by the ROHP-PAZ experiment. The GNSS PRO technique was confirmed further in an experimental field campaign from a mountain top (Padullés et al, 2016a). A preliminary data-processing technique to resolve precipitation structures from GNSS PRO was introduced by Padullés et al (2016b), but they showed that it would work only under certain limited conditions.…”
mentioning
confidence: 97%
“…Since precipitation-sized hydrometeors are typically aspherically shaped, the differential phase of the received signal is modified during tangential propagation through clouds associated with heavy precipitation. In the case of PRO, propagation through liquid precipitation or large crystalline ice (Vivekanandan et al, 1994) will induce a cross-polarized component (Padullés et al, 2016a). The measurement of differential propagation phase shifts has been studied in detail by the ground-based weather radar community (Bringi et al, 1990) and is now an integral part of the USA nationwide Next-Generation Radar (NEXRAD) radar system (e.g.…”
mentioning
confidence: 99%
“…The vertical information in RO additionally detects the vertical changes in stability to convection and discriminates what atmospheric layers control rain. RO profiles can thus improve our understanding of global processes internal to precipitating clouds when they are collocated with precipitation information, as done here with TRMM, or in the future with Polarimetric RO (Cardellach et al, ; Padullés et al, ) as planned with the PAZ satellite, or with cloud information as given by CloudSat.…”
Section: Discussionmentioning
confidence: 99%
“…The study performed in Cardellach et al [2015] demonstrated not only that heavy rain events could be detected, but also that an approximated vertical structure of the rain cell could be retrieved. The concept has been tested in a field campaign [Padullés et al, 2016] with promising results in views to the spaceborne mission. One of the limitations of this new concept is the ambiguity between the effect of the rain rate and the effect of the rain cell size, due to the along-path integrated nature of the RO observations.…”
Section: Introductionmentioning
confidence: 99%